A criança em abrigos: a proteção e o cuidado de bebês em acolhimento institucional - Lima, Mariana Parro [UNIFESP] (2019)
This research brought the reflection on the protection of babies in institutional foster care. This is a study of ethnographic inspiration that, by analyzing the concrete situation of 12 babies identified in a host institution in the municipality of Piracicaba, from 2015 to 2017, sought to capture the relationships and interactions that occurred there, then, to highlight the plots they raise, bringing together the complexities and contradictions that exist, both in the reality of the institutionalization of babies and young children, and in the discourse that supports it. The main objective of the research was to investigate how the experience of child shelter re-signifies, in current terms, the social meaning of the word protection and, as a result of this, sought to unveil the sense of protection that permeates concrete experiences of institutionalization. For that, the main theoretical references were the authors Fúlvia Rosemberg, Erving Goffman, and Robert Castel. The senses of protection and care employed by the different actors in the research scenario were discussed and, in the current context, are structuring aspects of the care of young children, when removed from their biological parents. We sought to contribute to childhood studies, exploring the theme of resignification of child shelter as a social form of protection and care, and which express not only institutional aspects, but also a perspective to research the social construction of responsibility on children. The studied institution showed some possible ways when the concern with the child and his family becomes the focus of the practices and actions in the shelter. The research revealed that, in practice, little has been achieved in terms of working with families of origin, those in extreme conditions of social vulnerability. There is a complexity of its own only observable when observed "closely." Analyzing their occurrences, it is possible to deconstruct the idea of a naturalness that accompanies the representations of social structure as something natural and in a progressive march to assist everyone. It was concluded that the services available are precarious, with no investment by the government in new alternative care or abandonment prevention services methodologies.